PATRIMONIAL MANAGEMENT AND HABITAT: THE CASE OF SPANISH COOPERATION IN THE HISTORIC CENTER OF CUSCO (1999-2010) - Alfaro Aucca, Crayla (2018)
After it was declared Cultural Heritage of Humanity by UNESCO (1983), the world’s attention focusedon the Historic Center of Cusco. It is the heart of a city with numerous problems, especially in terms of its inhabitants’ inadequate living conditions: lack of sanitation and legal ordering, insecurity, deterioration of its social and physical infrastructure. In light of this reality, an initial effort was made to plan and regulate the city’s built heritage through the Master Plan of the Historic Center of Cusco (2005). The participation of the Spanish Agency of International Cooperation for Development (AECID) between 1999 and 2010, both in the recovery of housing as in the revitalization of urban environments and the institutional strengthening of the Provincial Municipality of Cusco, became one of the contemporary work experiences in the management of heritage space in Peru with the greatest coverage and influence. This article summarizes the research carriedout by the author on the AECID experience in living and institutional issues. It puts forth a view of how it helped improve the quality of life of the projects’ beneficiary participants and how these could be adapted to manage current problems.